Pengembangan Modul Materi Sistem Reproduksi Manusia Berbasis Reading, Questioning And Answering (Rqa) Guna Menunjang Pembelajaran Mandiri dan Keterampilan Berpikir Kritis Siswa - Nesha Anjani Zahrawani; Peni Suharti (PEDAGO BIOLOGI, 2018)
Abstract : This study aims to produce a product in the form of teaching material of human reproductive system based on RQA in order to support independent learning and critical thinking skills. The research and development of this learning resource were conducted at University of Muhammadiyah Surabaya that limited trial on class XI MIPA 7 SMA Muhammadiyah 2 Surabaya. The method of development of this research was 4-D model by Thiagarajan, et al (1974), covering Define, Design, Develop and Disseminate, but the research was only at Development stage. The results showed that the developed teaching material has scoring criteria, "very valid" and deserve to be used based on validity results by validity checkers and limited trials. Based on the result of validity, the expedience of content was the average score of 90.7% with very valid criteria and the expedience of presentation obtained an average score of 87.55% with very valid criteria. The teaching material meets the RQA criteria by obtaining an average score of 87.5% with very valid criteria. Components of critical thinking earned an average score of 83.3% with valid criteria. Based on the results of pretest, the value was obtained an average of 42,80 and the value of post-test was 92,2 on the average. Besides, based on result of questionnaire of learning independence, the students responded positively in the average of 51,2%. Based on the questionnaires, the students responded positively to teaching material developed obtained an average score of 99.3%.